2014
DOI: 10.1001/jamaophthalmol.2013.8204
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic Occlusion of the Ophthalmic Artery After Cosmetic Facial Filler Injections

Abstract: for the Korean Retina Society IMPORTANCE Iatrogenic occlusion of the ophthalmic artery and its branches is a rare but devastating complication of cosmetic facial filler injections.OBJECTIVE To investigate clinical and angiographic features of iatrogenic occlusion of the ophthalmic artery and its branches caused by cosmetic facial filler injections. DESIGN, SETTING, AND PARTICIPANTS Data from 44 patients with occlusion of the ophthalmic artery and its branches after cosmetic facial filler injections were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
147
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(165 citation statements)
references
References 27 publications
9
147
1
2
Order By: Relevance
“…This indicates an unfavourable prognosis of ophthalmoplegia from a facial filler injection. Whereas previous studies reported a worse visual prognosis and more frequent cerebral infarctions with the use of autologous fat as a filler material than with hyaluronic acid (Park et al 2014), further progression of the emboli beyond the ophthalmic artery and resultant cerebral infarctions did not occur in our patients with hyaluronic acid injection. However, all the patients including the one who had intra-arterial thrombolysis using hyaluronidase remained without light perception in the involved eye during the follow-up of more than 8 months.…”
Section: Ophthalmoplegia As a Complication Of Cosmetic Facial Filler contrasting
confidence: 89%
See 2 more Smart Citations
“…This indicates an unfavourable prognosis of ophthalmoplegia from a facial filler injection. Whereas previous studies reported a worse visual prognosis and more frequent cerebral infarctions with the use of autologous fat as a filler material than with hyaluronic acid (Park et al 2014), further progression of the emboli beyond the ophthalmic artery and resultant cerebral infarctions did not occur in our patients with hyaluronic acid injection. However, all the patients including the one who had intra-arterial thrombolysis using hyaluronidase remained without light perception in the involved eye during the follow-up of more than 8 months.…”
Section: Ophthalmoplegia As a Complication Of Cosmetic Facial Filler contrasting
confidence: 89%
“…Our patients showed a relative sparing of the lateral rectus muscle, while previous studies reported total ophthalmoplegia after filler injections (Kim & Choi 2013;Park et al 2014). Occlusion of the medial/inferior muscular trunk arising from the ophthalmic artery paralyses the medial and inferior recti and inferior oblique muscles, while obstruction of the lateral/superior trunk causes palsies of the levator palpebrae, superior rectus and superior oblique muscles.…”
Section: Ophthalmoplegia As a Complication Of Cosmetic Facial Filler supporting
confidence: 41%
See 1 more Smart Citation
“…Most cases in Asia are documented in South Korea, where filler injections are common. (3) However, case reports have also emerged from China. While injections into other facial sites (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…2). (3,4,11,12) Understanding the specific anatomical planes at the area of injection is also important. For the nose, the supraperiosteal or supraperichondrial planes are relatively bloodless.…”
Section: Introductionmentioning
confidence: 99%